Minireview: Nuclear Receptor-Controlled Steroid Hormone Synthesis and Metabolism - He, Jinhan (The Endocrine Society, 2010)
Steroid hormones are essential in normal physiology whereas disruptions in hormonal homeostasis represent an important etiological factor for many human diseases. Steroid hormones exert most of their functions through the binding and activation of nuclear hormone receptors (NRs or NHRs), a superfamily of DNA-binding and often ligand-dependent transcription factors. In recent years, accumulating evidence has suggested that NRs can also regulate the biosynthesis and metabolism of steroid hormones. This review will focus on the recent progress in our understanding of the regulatory role of NRs in hormonal homeostasis and the implications of this regulation in physiology and diseases.